Genetic variability and association analysis in induced mutants of hard and soft hexaploid wheat (Triticum aestivum L.) under northern hill conditions - Sharma, Rohit Kumar; Rana, Vijay; Sood, V K; Sharma, Priya; Priyanka; Rana, Amit; Gupta, Chetan; Sharma, Akriti (Journal of Cereal Research, 2024)
The present study was conducted during Rabi 2021-22 to study variability, correlation and path coefficients for twelve morphological characters on 90 morphologically distinct mutants in M2 generation along with 6 checks in augmented block design at the Rice and Wheat Research Centre, Malan. It was observed that days to 75% maturity, spike length, harvest index, grains/spike and 1000-grain weight showed significant positive correlation with grain yield per plant. Biological yield per plant showed highest value for direct effect followed harvest index, spike length, peduncle length, days to 75 % maturity and 1000- grain weight. Path analysis for, biological yield had highest direct effect followed by harvest index, grains/spike, spike length, peduncle length and days to 75% maturity, peduncle length and 1000-grain weight.